Gene expression shifts in yellow-bellied marmots prior to natal dispersal. (17th December 2018) - Armenta, Tiffany C; Cole, Steve W; Geschwind, Daniel H; Blumstein, Daniel T; Wayne, Robert K
Abstract: The causes and consequences of vertebrate natal dispersal have been studied extensively, yet little is known about the molecular mechanisms involved. We used RNA-seq to quantify transcriptomic gene expression in blood of wild yellow-bellied marmots ( Marmota flaviventer ) prior to dispersing from or remaining philopatric to their natal colony. We tested 3 predictions. First, we hypothesized dispersers and residents will differentially express genes and gene networks since dispersal is physiologically demanding. Second, we expected differentially expressed genes to be involved in metabolism, circadian processes, and immune function. Finally, in dispersing individuals, we predicted differentially expressed genes would change as a function of sampling date relative to dispersal date. We detected 150 differentially expressed genes, including genes that have critical roles in lipid metabolism and antigen defense. Gene network analysis revealed a module of 126 coexpressed genes associated with dispersal that was enriched for extracellular immune function. Of the dispersal-associated genes, 22 altered expression as a function of days until dispersal, suggesting that dispersal-associated genes do not initiate transcription on the same time scale. Our results provide novel insights into the fundamental molecular changes required for dispersal and suggest evolutionary conservation of functional pathways during this behavioral process. Abstract : When individuals disperse from their safe home environment, they travel across unknown terrain with no reliable resources, encounter potentially dangerous predators and conspecifics, and are exposed to novel immune challenges. We found that marmots prepare for these risks at the molecular level by regulating expression of genes involved in metabolism and immunological defense before they leave home.